Effectiveness of Pro-Environmental Interventions to Improve Ecological Behavior - Tri Sulastri; St. Ichlasatul Amaliah R.; Muh. Alif Wirawan N.; Sadya Sarira Ayu; Yuyun Widia Wati (ARRUS Journal of Social Sciences and Humanities, 2024)
This research aims to determine the effectiveness of Pro-Environmental Behavior intervention in improving ecological behavior. The interventions provided are in the form of psychoeducation and individual tasks related to aspects of pro-environmental behavior which include recycling, energy conservation, and vicarious social behavior towards conservation. This research uses a quasi-experimental method with a one-group pretest-posttest design. Sampling was carried out using a purposive sampling method which was determined through inclusion and exclusion criteria. The participants selected in this study were 8 members of Fishing Community X who showed low ecological behavior as measured by the General Ecological Behavior Scale (GEB). The data analysis used in testing the pre-test and post-test data was the paired sample t-test. In this study, t-count > t-table was obtained, namely 8,683 > 2.365. The results of this analysis show that pro-environmental behavior interventions have proven effective in improving the ecological behavior of research participants through providing psychoeducation and activities that provide benefits to the environment.